Perimeter as relaxed Minkowski content in metric measure spaces. (April 2017) - Ambrosio, Luigi; Di Marino, Simone; Gigli, Nicola
Abstract: In this note we prove that on general metric measure spaces the perimeter is equal to the relaxation of the Minkowski contents w.r.t. convergence in measure.